Perhitungan Biaya Produksi sebagai Alat untuk Menentukan Harga Pokok Pesanan Kitchen Set pada CV. Java Home Decor - Esther Yulianawati Setiawan; Nurita Affan; Indra Suyoto Kurniawan (Jurnal Ilmu Akuntansi Mulawarman (JIAM), 2017)
The problem faced is whether the production cost of kitchen set which applied in the company already have appropriate with cost of goods ordered method based in cost accounting theory. The aim of this study is to analyze suitability of production cost with cost of goods ordered based accounting theory to CV Java Home Décor. The analytical tool used in this study is the job order costing method. In testing validity of comparing the calculation with the calculation based on analysis firm. The results of this study showed that calculation of cost of goods ordered manufactured by the company to goods kitchen set is Rp.63.577.000,00 and according the analysis Rp 66,615,040.00 so there is a difference Rp. 3,037,190.00. In this case can be seen that company establish manufacturing overhead costs set too low, should the cost of supporting the production process, either directly or indirectly be included in the calculation of the cost of production of each order.Keywords: Cost of Goods, Job Order Costing Method.